Haziqah’s Bakery / Nurul Ain Haziqah Mohamad Syahmi - Mohamad Syahmi, Nurul Ain Haziqah (2021)
Haziqah’s Bakery offer to its customer a handmade custard and pastry which are within the affordable price in order to caught the customer’s attention. Not to mention, Haziqah’s Bakery are also constantly making a sale or a special deal to letting the customer know regarding the new product by Haziqah’s Bakery Haziqah’s Bakery specifically targeted those people who are a pastry, a custard, a milk, and also a cheese lover. The bakery is also offered a cash on delivery (COD) service for those who lives within Gombak area and are unable to paid via online payment. From times to times, Haziqah’s Bakery also shared a post regarding any information that circulating the products that are being released by Haziqah’s Bakery itself. Facebook page is the platform that Haziqah’s Bakery choose to engage with the potential customer from introduce the products, promoting, and selling the products. The pages are being regularly updated in order to make the customer know about the existence of the products which are the Baked Milk and Baked Milk Cheese.